Analisis Sebaran Air Lindi Terhadap Kualitas Air Sumur Di Sekitar TPA Sukosari, Karanganyar - Yuli Pratiwi; Ravi Mardiyan; Paramita Dwi Sukmawati (Jurnal Serambi Engineering, 2022)
Landfill activities can produce leachate water that can be infiltrated into the soil so that it can pollute the surrounding well water.. This study aims to map the distribution of leachate water to the quality of shallow groundwater around TPA. Sampling of well water owned by residents is 100-700 meters from the TPA and 2 leachate water sample points of the Sukosari TPA. The parameters of leachate water and well water analyzed include, pH, BOD, COD. The quality standard for shallow groundwater quality used is the class I quality standard of Government Regulation No.82 of 2001, while the leachate water quality standard used is the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia No P.59 / Menlhk / Setjen / Kum.1 / 7/2016. The quality of shallow groundwater around the Sukosari TPA is polluted with leachate water judging from the parameters of pH, BOD and COD. The pH parameter does not meet the quality standards, the BOD value that meets the quality standards is only 6.7,8.9. COD value that meets the quality standards is only the location of the well 7. The effect of leachate water derived from the Sukosari TPA on well water quality showed a positive correlation for the pH parameter, namely with a value coefficient of 0.911 and for the BOD and COD parameters showed a negative correlation, namely with a BOD value of -0.657 and a COD value of -0.628 and there was a significant relationship. Map data processing techniques with Kriging and IDW interpolation methods.Keywords: groundwater, shallow groundwater quality, litter, TPA.